Correlation between severity of symptoms and degree of radiologic stenosis in adults with degenerative lumbar spine stenosis - Hart, Idawarifagha; Okwunodulu, Okwuoma; Ajare, Enyereibe C.; Ohaegbulam, Samuel C. (International Surgery Journal, 2025)
Background: Degenerative lumbar spine stenosis (LSS) is an increasing cause of morbidity in an ever-ageing population. Correlation of the severity of symptoms with the degree of radiologic stenosis has yielded mixed results. This study aims to correlate the severity of symptoms and degree of radiologic stenosis in adults with degenerative LSS. Methods: This was a prospective cross-sectional study. Patients recruited were those who had degenerative LSS who gave consent to partake in this study. Patients with lumbar spine stenosis from trauma, infection, tumours, and patients with previous lumbar spine surgery, cerebrovascular accident, motor neuron or demyelinating disease were excluded. Clinical LSS was assessed using the NCOS questionnaire and radiologic LSS severity was categorized using the stenosis ratio (quantitative) and the Shcizas grades (qualitative) obtained from 1.5T magnetic resonance imaging (MRI) scans. Ethical approval was obtained for this study. Results: Fifty patients participated in this study, 22 males and 28 females. Mean age was 58.4±10.8 years. Sixty-six percent of patients had multilevel stenoses, and L4/5 was the most affected level with critical stenosis (62%). LSS clinical features, as demonstrated by the NCOS, did not correlate significantly with the stenosis ratio (r=0.094, p=0.523). Furthermore, the correlation between the NCOS and the Schizas grade was not statistically significant, rs=-0.187, p=0.202. Conclusion: Severity of symptoms in degenerative LSS poorly correlates with the degree of radiologic stenosis. Hence clinical and radiologic assessments should guide patient’s care.